Overlap and temporal variation in the diets of sympatric Antarctic and Subantarctic fur seals (Arctocephalus spp.) at Marion Island, Prince Edward Islands. Issue 1 (1st January 2018) - Reisinger, Ryan R.; Landman, Marietjie; Mgibantaka, Nonkoliso; Smale, Malcolm J.; Bester, Marthán N.; De Bruyn, P.J. Nico; Pistorius, Pierre A.
ABSTRACT: Antarctic ( Arctocephalus gazella ) and Subantarctic ( A. tropicalis ) fur seals are important predators in the Southern Ocean. Marion Island (southern Indian Ocean) hosts the largest sympatric breeding populations of these two species. Environmental and population changes here over two decades may have influenced their diet and trophic interactions. To quantify diet, we analysed prey remains in scat samples from Antarctic (661 scats) and Subantarctic (750 scats) fur seals collected at Marion Island (2006–2010). We assessed diet composition over time and calculated dietary overlap. The diet of both species was dominated by fish prey (98.2% and 99.4% of prey items), mainly myctophids. Antarctic fur seals consumed small numbers of penguins, cephalopods and crustaceans. In Subantarctic fur seal scats, crustaceans and cephalopods were rare and penguin remains were absent. The diets of the two species overlapped substantially (Pianka's index = 0.98), however, small but significant differences in the relative proportions of prey were evident. Seasonal and annual diet changes suggest that their diet is similarly influenced by patterns of local prey availability and abundance. Despite substantial changes in the population size and trajectory of Antarctic and Subantarctic fur seals – which would be expected to influence trophic interactions between them – comparing our data to those from earlier studies (1989–2000) did not reveal significant long-term dietary changes in either species.